Gambaran Asuhan Keperawatan pada Klien yang Mengalami Hipertermi dengan Dengue Haemorrhagic Fever di RS Bhakti Asih - Andi Saputra; Revie Fitria Nasution (STIKes Persada Husada Indonesia, 2021)
Dengue hemorrhagic fever (DHF) is a very common disease in Indonesia and other tropical countries. This disease is more common in urban and sub-urban areas. In 2013 there were reported as many as 2.35 million cases in America, of which 33,687 cases were severe dengue. (WHO, 2016). The case fatality rate (CFR) in the early years of dengue cases spreading in Indonesia was very high. Then from year to year it began to decline from 41.4% in 1968 and continued to decline to 0.89% in 2009. The purpose of this study was to obtain an overview of the implementation of nursing care for clients experiencing Hyperthermia with Dengue Haemorragic Fever at Bhakti Asih Hospital. The design of this research is descriptive qualitative without intervention. This research was carried out at the Bhakti Asih Hospital, when the research was carried out on July 10-13 2019. A literature review was carried out both in print and online. Data analysis using tri angulation. The assessment on Mr. R who had DHF had symptoms of an increase in body temperature of 38.80C, with symptoms of fluid deficiency. There are some theoretical signs and symptoms that do not appear, namely seizures and decreased consciousness. At this stage of diagnosis, 4 nursing diagnoses were found. At the planning stage, the priority diagnosis equations were found in theory. No special implementation was carried out in the case of Mr. R. At the evaluation stage, based on the results of previous studies, it was stated that giving warm compresses was very effective in reducing hyperthermia.